2007
DOI: 10.1111/j.1460-9568.2007.05769.x
|View full text |Cite
|
Sign up to set email alerts
|

d‐Amino acid oxidase and serine racemase in human brain: normal distribution and altered expression in schizophrenia

Abstract: The N-methyl-d-aspartate receptor co-agonist d-serine is synthesized by serine racemase and degraded by d-amino acid oxidase. Both d-serine and its metabolizing enzymes are implicated in N-methyl-d-aspartate receptor hypofunction thought to occur in schizophrenia. We studied d-amino acid oxidase and serine racemase immunohistochemically in several brain regions and compared their immunoreactivity and their mRNA levels in the cerebellum and dorsolateral prefrontal cortex in schizophrenia. dAmino acid oxidase im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
183
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(201 citation statements)
references
References 85 publications
14
183
2
2
Order By: Relevance
“…We speculate that the differences in efficacy between these mechanisms may stem from dissimilarities in CNS localization of GlyT1 and DAAO. GlyT1 is heavily expressed in forebrain regions rich in NMDA receptors (Smith et al, 1992), whereas DAAO is expressed primarily in the hindbrain and cerebellum (Verrall et al, 2007). Thus, the high density of GlyT1 in the cortex and the close proximity of GlyT1 to the synapse (Cubelos et al, 2005) may produce a greater increase in NMDA receptor transmission resulting from GlyT1 inhibition, relative to DAAO inhibition.…”
Section: Discussionmentioning
confidence: 98%
“…We speculate that the differences in efficacy between these mechanisms may stem from dissimilarities in CNS localization of GlyT1 and DAAO. GlyT1 is heavily expressed in forebrain regions rich in NMDA receptors (Smith et al, 1992), whereas DAAO is expressed primarily in the hindbrain and cerebellum (Verrall et al, 2007). Thus, the high density of GlyT1 in the cortex and the close proximity of GlyT1 to the synapse (Cubelos et al, 2005) may produce a greater increase in NMDA receptor transmission resulting from GlyT1 inhibition, relative to DAAO inhibition.…”
Section: Discussionmentioning
confidence: 98%
“…Second, in a 6-week double-blind, placebo-*Address correspondence to this author at the Division of Clinical Neuroscience, Chiba University Center for Forensic Mental Health, 1-8-1 Inohana, Chiba 260-8670, Japan; Tel: +81-43-226-2147; Fax: +81-43-226-2150; Email: hashimoto@faculty.chiba-u.jp controlled study, Tsai et al [27] reported that D-alanine (100 mg/kg/day) significantly improved schizophrenic symptoms when used as adjunctive to conventional antipsychotic drugs. Third, mRNA expression and activity of D-amino acid oxidase (DAAO), which can metabolize D-alanine, is increased in the postmortem brain of schizophrenic patients [28,29]. Fourth, the G72 gene on the chromosome 13q was significantly associated with schizophrenia [30].…”
Section: Introductionmentioning
confidence: 99%
“…6,53-55 Accordingly, increased mRNA expression and activity of the enzyme responsible for the degradation of this D-amino acid, D-amino acid oxidase, have been observed in the postmortem brain of SCZ subjects. 8,56 Recent evidence suggests that the atypical amino acid D-Asp, enriched in the embryo brain, promotes NMDAR-dependent transmission. 38 Consistent with the hypothesis of NMDAR dysfunction in SCZ, [1][2][3][4] we have previously found reduced levels of D-Asp in the postmortem PFC of SCZ patients.…”
Section: Discussionmentioning
confidence: 99%